2021
DOI: 10.1108/jmlc-08-2021-0085
|View full text |Cite
|
Sign up to set email alerts
|

Money laundering, food activities and mafia: evidences from the Italian provinces

Abstract: Purpose According to the INTERPOL definition, money laundering is: “any act or attempted act to conceal or disguise the identity of illegally obtained proceeds so that they appear to have originated from legitimate sources”. Along this line, the purpose of this paper is to investigate the link amongst money laundering, mafia and food activities, in the Italian provinces. Design/methodology/approach By using annual data over the period 2010 to 2018, the author estimates balanced panel data using the instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In reality, differing views are expressed by scholars concerning the effectiveness of AML legal and regulatory framework and their effect on illegal activities. One recent study concerns the research conducted by Olivia (2021) who sought to investigate the link amongst money laundering, mafia and food activities in Italy. The author used panel data between the years 2010 and 2018 through instrumental variables approach and the findings revealed that ongoing monitoring and effective implementation of AML laws, especially by the police force are indeed very effective in discouraging money laundering in most parts of Italy.…”
Section: Effectiveness Of Anti-money Laundering Legal and Regulatory ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, differing views are expressed by scholars concerning the effectiveness of AML legal and regulatory framework and their effect on illegal activities. One recent study concerns the research conducted by Olivia (2021) who sought to investigate the link amongst money laundering, mafia and food activities in Italy. The author used panel data between the years 2010 and 2018 through instrumental variables approach and the findings revealed that ongoing monitoring and effective implementation of AML laws, especially by the police force are indeed very effective in discouraging money laundering in most parts of Italy.…”
Section: Effectiveness Of Anti-money Laundering Legal and Regulatory ...mentioning
confidence: 99%
“…However, the financial mode of money laundering was first practiced in the USA in the early 1900’s when gangs like Al Capone bought Laundromats to filter black money from illegal activities and mix the proceeds with the lawful business funds to make it appear legitimate. Indeed, Meyer Lansky was recognised as the Father of Money Laundering since he was convicted of laundering money by placing his funds in Swiss bank and later transferred them to various foreign banks, in the process of portraying them as legitimate (Paxton, 2015). Consequently, the US Bank Secrecy Act 1970 (BSA) was the first legislation to be created to combat and prevent money laundering activities (Anderson and Anderson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, uno de los problemas principales de estas actividades criminales es la inversión del dinero obtenido o acumulado, que ha llevado a utilizar el intercambio comercial, financiero y uso de prestanombres, para encubrir el origen ilícito del dinero. A esta operación es la que denominamos lavado de activos o blanqueamiento de dinero (Oliva, 2021). Según el Grupo de Acción Financiera (GAFI), lo denomina al lavado de activos al conjunto de procedimientos que utilizan para ocultar el origen ilícito de ingresos producidos por el delito, para legitimizar las ganancias obtenidas del mismo.…”
Section: Introductionunclassified